Aliskiren alone or in combination with enalapril vs. enalapril among patients with chronic heart failure with and without diabetes: a subgroup analysis from the ATMOSPHERE trial. (25th September 2017) - Kristensen, Søren L.; Mogensen, Ulrik M.; Tarnesby, Georgia; Gimpelewicz, Claudio R.; Ali, Mohammed A.; Shao, Qing; Chiang, YannTong; Jhund, Pardeep S.; Abraham, William T.; Dickstein, Kenneth; McMurray, John J.V.; Køber, Lars
Abstract : Aims: Because of concerns about the safety of aliskiren in patients with diabetes, study treatment was stopped prematurely in the Aliskiren Trial of Minimizing OutcomeS for Patients with HEart failuRE (ATMOSPHERE). We examined outcomes and treatment effect in these patients compared with those without diabetes. Methods and results: ATMOSPHERE included 7016 patients with heart failure and a reduced ejection fraction (HFrEF) randomly assigned to enalapril plus aliskiren, aliskiren alone, or enalapril. At baseline, 1944 (27.7%) patients had diabetes. Median follow‐up was shorter in patients with diabetes compared with those without (24 months vs. 46 months). Among patients with diabetes, the primary endpoint of cardiovascular death or hospitalization for heart failure occurred in 216 patients (33.1%) in the enalapril group (reference), 172 (27.4%) in the aliskiren group [hazard ratio (HR) 0.82, 95% confidence interval (CI) 0.67–1.00; P = 0.053], and 196 (29.5%) in the combination group (HR 0.86, 95% CI 0.71–1.04; P = 0.13). The effects of the treatments studied did not differ significantly compared with patients without diabetes. In patients with diabetes, aliskiren monotherapy was associated with a lower risk of symptomatic hypotension compared to enalapril [42 (6.7%) vs. 65 (10.0%); P = 0.04], whereas other adverse events were generally balanced between the three groups. Conclusion: In patients with HFrEF and diabetes, there was no signal of harm and a trend towards benefit when direct renin inhibition monotherapy was compared with an angiotensin‐converting enzyme inhibitor, whereas combined aliskiren and enalapril treatment led to more adverse events with no improvement in outcomes. Treatment effects did not differ in patients with diabetes compared with those without. Clinical Trial Registration URL:http://www.clinicaltrials.gov . Unique identifier: NCT00853658.